A Phytochemical Perspective on Plant Defense Against Nematodes - Desmedt, Willem; Mangelinckx, Sven; Kyndt, Tina; Vanholme, Bartel (Frontiers in Plant Science, 2020)
Given the large yield losses attributed to plant-parasitic nematodes and the limited availability of sustainable control strategies, new plant-parasitic nematode control strategies are urgently needed. To defend themselves against nematode attack, plants possess sophisticated multi-layered immune systems. One element of plant immunity against nematodes is the production of small molecules with anti-nematode activity, either constitutively or after nematode infection. This review provides an overview of such metabolites that have been identified to date and groups them by chemical class (e.g., terpenoids, flavonoids, glucosinolates, etc.). Furthermore, this review discusses strategies that have been used to identify such metabolites and highlights the ways in which studying anti-nematode metabolites might be of use to agriculture and crop protection. Particular attention is given to emerging, high-throughput approaches for the identification of anti-nematode metabolites, in particular the use of untargeted metabolomics techniques based on nuclear magnetic resonance (NMR) and mass spectrometry (MS).